Desenvolvimento de um modelo de processos de gestão de contratos com fornecedores - Moura, Luciane Oliveira de (Universidade do Vale do Rio dos Sinos, 2010)
The use of a model of contract management, contemplating assignments, processes, indicators, and that have a way of centralizing its controls, offers many benefits for the resource management of IT. Companies that have a way of managing their contracts avoid unnecessary risks, such as: extra payment of fares, contractual penalty, image damage, risks of contingency of resources, operation limits, unawareness of important terms, which may lead people to buy an inferior service differing from the one specified in the deal. As the investments in technology reach high costs in the companies, the administration of IT contracts become indispensable nowadays. Based on the current situation of the companies, which many times do not have updated or relevant information about their contracts with suppliers, a contractual management model will be developed contemplating the life cycle of a contract. In order to understand this process, there will be an approach on a literature review about contract management, and of the models PMBOK (Project Management Body of Knowledge) and BPM (Business Process Management) that together will help the development of this model based on processes, supporting all the activities related to IT contract management. Based on the creation of this model, there will be possible to establish processes, having a model that define assignments, indicators working with tools that make these activities automated, making it possible for the contracts to monitored during all this life cycle. With the implementation of a model of contract management and having knowledge on what has been contracted, the companies will be able to evaluate their investments, having as benefits, the control and knowledge of the contracts made between the company and the suppliers, cost reduction, regulatory standards compliance, making it possible to value assets and avoid downtime and emergency spending.
Keywords: Modelo de gestão; Gestão de contratos; Ciclo de vida; Processos; Management model; Contract management; Life cycle; Processes